2020
DOI: 10.3390/buildings10080134
|View full text |Cite
|
Sign up to set email alerts
|

Schedule Delay Risk Analysis in Construction Projects with a Simulation-Based Expert System

Abstract: In this paper, we present a simulation-based approach for effectively estimating delay risks in project schedules and predicting the possibilities of in-time project completion for various deadlines. The main contribution of this study is the development of a novel approach for duration risk quantification, which uses a newly introduced equation for total risk estimation regarding activities’ durations, and quantifying the manager’s experience as expressed through a questionnaire. In addition, the proposed app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…These are just a few examples, of which there are many more. A very thorough overview of many construction-related studies based on Monte Carlo simulations can be found in the paper by Koulinas et al [95].…”
Section: Time-at-risk (Tar) and Monte Carlo Simulationmentioning
confidence: 99%
“…These are just a few examples, of which there are many more. A very thorough overview of many construction-related studies based on Monte Carlo simulations can be found in the paper by Koulinas et al [95].…”
Section: Time-at-risk (Tar) and Monte Carlo Simulationmentioning
confidence: 99%
“…One of the most striking problems concerning the existing delay analysis models identified by the researchers is ignoring the CPM during the computation of delay and designation of it to the responsible parties [92,93]. Additionally, actualized schedules may contradict with the planned schedule [94]; therefore, disregarding the actual site progress cannot give the accurate result for delay analyses [95,96]. Actual progress consideration for the time intervals is also vital to detect the fluctuations on the Critical Path (CP) during the execution of delay analysis [12,92,97].…”
Section: Framework Of Existing Delay Analysesmentioning
confidence: 99%
“…Project scheduling and the allocation of limited resources to activities is one of the most important topics related to the field of project management. Koulinas et al [13] proposed a simulation-based method for determining risks of schedule delay. In addition, Abdellatif and Alshibani [14] specified the main causes of project delays in Saudi Arabia.…”
Section: Project Schedulingmentioning
confidence: 99%